(untitled) (Eurasian Research Bulletin, 2023)
This article discusses the significance of SPM in patients with traumatic brain injury, changes in the respiratory and cardiovascular systems of the patient’s body after prolonged mechanical ventilation. In total, 295 patients with craniocerebral injuries have been treated in the Department of Neuro-Resuscitation of the Republican Scientific Center for Emergency Medical Assistance to the Bukhara branch this year. In 85 of these patients, an IVDS device was connected. During the examination of 49 patients, 20 showed various changes in the cardiovascular and respiratory systems. The article describes X-ray studies, laboratory studies and ECG changes in these patients.